2023
DOI: 10.1128/jvi.00802-23
|View full text |Cite
|
Sign up to set email alerts
|

Human astrovirus capsid protein releases a membrane lytic peptide upon trypsin maturation

Abstract: The human astrovirus (HAstV) is a non-enveloped, single-stranded RNA virus that is a common cause of gastroenteritis. Most non-enveloped viruses use membrane disruption to deliver the viral genome into a host cell after virus uptake. The virus–host factors that allow for HAstV cell entry are currently unknown but thought to be associated with the host-protease-mediated viral maturation. Using in vitro liposome disruption analysis, we identified a trypsin-dependent lipid disruption activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Residues 297–347 that were not identified by mass spectrometry map to this outer region, suggesting that they are accessible on the surface of the assembled virus capsid for protease cleavage. It is interesting to note that residue E296, the last VP33 residue observed by mass spectrometry, is in a structurally similar location as a putative trypsin maturation cleavage site in classical HAstVs (R313 in HAstV-8) that is thought to be important for exposing a membrane-lytic peptide ( Fig 4C and 4D ) [ 59 ]. Next, we observed that VP38 amino acids include the C-terminal end of the predicted HAstV-VA1 capsid core structural domain, a predicted linker region, and the full spike domain ( Fig 4C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Residues 297–347 that were not identified by mass spectrometry map to this outer region, suggesting that they are accessible on the surface of the assembled virus capsid for protease cleavage. It is interesting to note that residue E296, the last VP33 residue observed by mass spectrometry, is in a structurally similar location as a putative trypsin maturation cleavage site in classical HAstVs (R313 in HAstV-8) that is thought to be important for exposing a membrane-lytic peptide ( Fig 4C and 4D ) [ 59 ]. Next, we observed that VP38 amino acids include the C-terminal end of the predicted HAstV-VA1 capsid core structural domain, a predicted linker region, and the full spike domain ( Fig 4C ).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, our mass spectrometry data support that the HAstV-VA1 capsid becomes cleaved in one or more places in the outer region of the capsid core domain, which forms the shell of the virus capsid. Recent studies suggest that this proteolytic processing in HAstVs may expose a membrane-lytic peptide utilized for host membrane disruption during cell entry [ 59 ]. Our data support that HAstV-VA1 utilizes a similar mechanism to promote infectivity.…”
Section: Discussionmentioning
confidence: 99%